Improving Science Learning Outcomes Through Audiovisual Media at Grade V SDN 011 Pondok Gelugur - Muhammad Permadi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The problem that occurs at SD Negeri 011 Pondok Gelugur is the lack of interest and attention of students in participating in learning, so that students' initial learning results do not reach the predetermined KKM limits.Objective: This research is Classroom Action Research (PTK) which aims to determine whether the application of audio-visual media in learning about food digestive organs in humans can improve learning outcomes for class V students at SD Negeri 011 Pondok Gelugur.Method: Classroom action research conducted in 2 cycles consists of four main research components, namely: planning; implementation; data collection; and reflection. The research subjects were class V (Fifth) students with 4 male and 6 female students for the 2024/2025 academic year. Data analysis was conducted using learning mastery percentage. The success indicator was defined as a minimum of 80% of students achieving the KKM score.Results: In cycle I, the learning outcomes of students were known to be 5 students who achieved a score above the KKM with an average class score of 71.5. Furthermore, in cycle II improvement activities, student learning outcomes increased to 9 students achieving scores above the KKM with an average class score of 76.5.Conclusion: The conclusion is that the use of audio-visual media makes learning more interesting and can increase students' interest and learning outcomes in science subjects, and learning objectives can be achieved well as evidenced by the significant increase in student learning outcomes.